2002
DOI: 10.1128/jb.184.18.5027-5035.2002
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Histidine-Rich CPx-ATPase from the Filamentous Cyanobacterium Oscillatoria brevis Related to Multiple-Heavy-Metal Cotolerance

Abstract: A novel gene related to heavy-metal transport was cloned and identified from the filamentous cyanobacterium Oscillatoria brevis. Sequence analysis of the gene (the Bxa1 gene) showed that its product possessed high homology with heavy-metal transport CPx-ATPases. The CPC motif, which is proposed to form putative cation transduction channel, was found in the sixth transmembrane helix. However, instead of the CXXC motif that is present in the N termini of most metal transport CPx-ATPases, Bxa1 contains a unique C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 38 publications
(54 reference statements)
3
37
0
Order By: Relevance
“…Although similar motifs were found in TcHMA4-C and AtHMA4-C, this domain is also the most divergent part between the two sequences. CC dipeptides were only found, together with a His-rich domain, in the N-terminal region of bacterial CPx-ATPases and were associated with Cd 2þ tolerance [28,29]. The function of these putative heavy metal binding motifs remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although similar motifs were found in TcHMA4-C and AtHMA4-C, this domain is also the most divergent part between the two sequences. CC dipeptides were only found, together with a His-rich domain, in the N-terminal region of bacterial CPx-ATPases and were associated with Cd 2þ tolerance [28,29]. The function of these putative heavy metal binding motifs remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…All these three peptides also contained three additional cysteine motifs -C(x) 4 C, C(x) 3-5 CC, CC -and a His rich domain within their extended C-terminus which could be involved in heavy metal binding. Further examination of the two putative HMA4 COOH tails revealed that the C(x) 3 CC motifs were in a larger cysteine motif, C(x) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] C(x) 3 CC for Thlaspi and C(x) [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] C(x) 3 CC for Arabidopsis. This sequence is similar to the recently described TRASH domain, C(x) [19][20][21][22] C(x) 3 C, predicted to be involved in heavy metal sensing, trafficking and resistance [25].…”
Section: Isolation Of T Caerulescens Hma4 Cdnamentioning
confidence: 99%
“…HMA1 lacks the N-terminal Heavy Metal Associated regulatory domain usually found in P 1B -ATPases. Instead, it has a long His stretch reminding the N-terminal domain of the P 1B-2 Bxa1 from Oscillatoria brevis that was described as transporting both copper and zinc (41).…”
Section: Discussionmentioning
confidence: 99%
“…The P 1B subfamily of ATPases is believed to be involved in the transport of heavy metals such as Zn, Cu, Co, Cd, Pb, and silver that are either essential micronutrients or noessential toxic metals, although only a few members of this subfamily have been well characterized. Genome sequencing efforts as well as isolation and analysis of individual members of this subgroup from different organisms indicate these heavy metal ATPases are expressed in a wide range of organisms, ranging from the archaea and bacteria to eukaryotic organisms including Arabidopsis (see, for example, Rensing et al, 1997;Palmgren, 1998, 2001;Tong et al, 2002;Mills et al, 2003).…”
Section: Tchma4 Confers Metal Tolerance In Yeast Via Metal Efflux Outmentioning
confidence: 99%